Characteristics of Emissions from Reclamation of Solid-recovered Fuel (SRF) in a Cogeneration Plant - Yi-Ming Kuo; Shih-Wei Huang; Wang Yu Kuan (Aerosol and Air Quality Research)
Abstract The feasibility of the replacement of coal with solid-recovered fuel (SRF) transformed from waste lubricants was investigated in this work. In addition, the emission characteristics of SRF reclamation in a cogeneration plant were evaluated. The raw waste lubricants collected from a factory that manufactures tinplate cans were pretreated, mixed with wood dust, bentonite, and coal ash, and then remolded into pellet SRF. The coal and remolded SRF were reclaimed in a cogeneration plant. The reclamation performance of the tested fuels was evaluated by analyzing the pollutant characteristics of the bottom ash, fly ash, and flue gas. The PCDD/F concentrations in the flue gas in the runs without coal (0.003 ng I-TEQ Nm−3) were slightly lower than those in the runs with coal (0.102 ng I-TEQ Nm−3). According to the monitoring data for CO, O2, NOx and combustion efficiency, the substitution of SRF for coal improved the combustion conditions. The results showed that transformation of waste lubricant into SRF for reclamation is a promising method by which to take both waste treatment and energy regeneration into consideration.